Transatlantic : a novel - McCann, Colum, 1965- (Random House, 2013)
A tale spanning 150 years and two continents reimagines the peace efforts of democracy champion Frederick Douglass, Senator George Mitchell and World War I airmen John Alcock and Teddy Brown through the experiences of four generations of women from a matriarchal clan.